Analisis Perbandingan Kinerja Keuangan antara Bank Syariah dan Bank Konvensional (Studi Kasus pada Bank Syariah Mandiri dan Bank Mandiri) - Yusvita Nena Arinta (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
This study aims to analyze the performance of Sharia Bank and ConventionalBank viewed from financial ratio and to find the significant difference comparedto the performance of Islamic Bank and Conventional Banks viewed from financial ratio. This is a quantitative research. The data were taken from banks that published annual financial reports namely PT Bank Syariah Mandiri and PT. Bank Mandiri from 2011 to 2015. The analysis technique used in this research is financial ratio and t test. The results of this study showed that there is a significant difference between the performance of PT. Bank Syariah Mandri compared with PT. Bank Mandiri and, PT. Bank Syariah Mandiri has a better performance compared to that of PT. Bank Mandiri